2023
DOI: 10.3390/polym15102335
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial Activities and Characterizations of Biosynthesized Zinc Oxide Nanoparticles, and Their Coated with Alginate Derived from Fucus vesiculosus

Abstract: Zinc oxide nanoparticles have many advantages for nano-biotechnologists due to their intense biomedical applications. ZnO-NPs are used as antibacterial agents, which influence bacterial cells through the rupture of the cell membrane and the generation of reactive free radicals. Alginate is a polysaccharide of natural origin due to its excellent properties that are used in various biomedical applications. Brown algae are good sources of alginate and are used as a reducing agent in the synthesis of nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Previous research has indicated that the Zn 2+ ion has strong antibacterial properties against various clinically important pathogens [39][40][41]. Furthermore, it has a vital role in osteoblast cell proliferation and differentiation, thus promoting bone healing [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that the Zn 2+ ion has strong antibacterial properties against various clinically important pathogens [39][40][41]. Furthermore, it has a vital role in osteoblast cell proliferation and differentiation, thus promoting bone healing [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The Sv/Ag-NPs solutions were characterized by using UV-visible, TEM Transmission Electron Microscope, X-ray diffraction patterns, Zeta potential, (EDS), and FT-IR, the model of all devices used in this study as in the previous study by Hamouda et al [69].…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 99%
“…Thus, that denotes the purity of ZnO-ED NPs photocatalysts. The sharp and limited crests demonstrated that the biosynthesized ZnO NPs were still exceedingly crystallized (Hamouda et al 2023).…”
Section: Xrd Analysismentioning
confidence: 99%